Design and simulation of three phase rectifier with power factor correction - Abdul Rahim, Muhd Halalluddin (2012)
The Switch Mode Power Supplies (SMPS) are a multi-million dollar industry and continuously growing industry within the field of power electronics. SMPS is widely been used in communication, computers and industrial. The Unity Power Factor (UPF) rectifier has become an important design issue as a consequence of recent legislation. European legislation restricts the harmonic content of power supplies. The advantages of UPF are more than legislative compliance. The advantages include greater efficiency, larger power density and improved power quality result in economic benefits to the electricity service provider. The goal of this thesis is to develop a unity power factor rectifier. The motivation in developing this product was to develop a regulated power supply capable of producing power with low level of harmonic current distortion. This project observes the current, voltage waveform and also the harmonics component before and after the compensation to the nonlinear load. In this work MATLAB/SIMULINK power system toolbox is used to simulate the proposed system. Simulation results are presented and the improvement in the supply current will show in this work.